Nurse leaders' and digital service developers' perceptions of the future role of artificial intelligence in specialized medical care: An interview study. (21st August 2022) - Laukka, Elina; Hammarén, Mira; Kanste, Outi
Abstract: Aim: To describe nurse leaders' and digital service developers' perceptions of the future role of artificial intelligence (AI) in specialized medical care. Background: Use of AI has rapidly increased in health care. However, nurse leaders' and developers' perceptions of AI and its future in specialized medical care remain under‐researched. Method: Descriptive qualitative methodology was applied. Data were collected through six focus groups, and interviews with nurse leaders ( n  = 20) and digital service developers ( n  = 10) conducted remotely in 2021 at a university hospital in Finland. The data were subjected to inductive content analysis. Results: The data yielded 25 sub‐categories, 10 categories and three main categories of participants' perceptions. The main categories were designated AI transforming: work, care and services and organizations. Conclusions: According to our respondents, AI will have a significant future role in specialized medical care, but it will likely reinforce, rather than replace, clinicians or traditional care. They also believe that it may have several positive consequences for clinicians' and leaders' work as well as for organizations and patients. Implications for nursing management: Nurse leaders should be familiar with the potential of AI, but also aware of risks. Such leaders may provide betters support for development of AI‐based health services that improve clinicians' workflows.